An autopsy case of corticobasal syndrome due to asymmetric degeneration of the motor cortex and substantia nigra with TDP‐43 proteinopathy, associated with Alzheimer's disease pathology. Issue 3 (3rd February 2021) - Tando, So; Kasai, Takashi; Mizuta, Ikuko; Takahashi, Hisashi; Yaoi, Takeshi; Saito, Kozo; Hojo, Tomohito; Mizuno, Toshiki; Hasegawa, Masato; Itoh, Kyoko
Abstract : We herein report a case of corticobasal syndrome (CBS) due to asymmetric degeneration of the motor cortex and substantia nigra with transactivation response DNA‐binding protein of 43 kDa (TDP‐43) proteinopathy, associated with Alzheimer's disease (AD) pathology. An 85‐year‐old man initially noticed that he had difficulty in walking and had trouble in moving his right hand and lower limb one year later. His gait disturbance was aggravated, and at the age of 87 years, his neurological examination revealed parkinsonism and positive frontal lobe signs. Brain magnetic resonance imaging (MRI) revealed atrophy of the left frontotemporal lobe and cerebral peduncle, and cerebral blood flow scintigraphy revealed hypoperfusion of the left frontotemporal lobe, leading to a possible diagnosis of CBS. At the age of 89 years, he was bedridden, and rarely spoke. He died of aspiration pneumonia five years after the onset of initial symptoms. At the autopsy, the brain weighed 1280 g and showed left‐sided hemiatrophy of the cerebrum and cerebral peduncle. Neuropathological examination revealed AD pathology (Braak AT8 stage V, Braak stage C, CERAD B, Thal classification 5). Phosphorylated TDP‐43 (p‐TDP‐43) immunohistochemistry revealed widespread deposits of dystrophic neurites (DNs), glial cytoplasmic inclusions (GCIs), and neuronal cytoplasmic inclusions (NCIs), which were most remarkable in layers II/III of the motor cortex and predominant on the left hemisphere of the frontal cortex, these neuropathology being consistent with frontotemporal lobar degeneration with TDP‐43 (FTLD‐TDP) type A. Interestingly, neuronal loss in the substantia nigra was more severe on the left than the right side, with a few phosphorylated tau (p‐tau) and p‐TDP‐43 deposits. It is highly likely that asymmetric TDP‐43 pathology rather than symmetric tau pathology contributed to the laterality of degeneration of the cerebral cortex, substantia nigra, and pyramidal tract, which led us to suggest that TDP‐43 proteinopathy might be a primary cause.